Knowledge, Attitude and Practice of Cervical Cancer Screening through Visual Inspection with Acetic Acid - Susmita Kar; Md. Kapil Ahmed (International Journal of Public Health Science (IJPHS), 2017)
Detection of the cervical cancer requires practice of screening that will increase survival rates from the disease. Visual Inspection with Acetic Acid (VIA) is an alternative to screening for cervical cancer.This study aims to assess the knowledge, attitude, and practice towards VIA screening among adult women. We used a cross-sectional study in urban areas of Bangladesh with a sample of 285 respondents those were interviewed through semi-structured questionnaire. Analyses have done by targeting the objectives and considering the indicators with appropriate test statsitsics.About 56.1% respondents aged between 18 and 35 years with majority had at least secondary education including 29.5% were from affluent group. Though the highest majority of women had the knowledge of cervical cancer but only quarter was aware of VIA. A few of the respondents adopted any screening test for detecting cervical cancer and this lower coverage could be due to, among other reasons, lack of knowledge, accessibility, and service availability. The results also indicated that higher educational level of respondents is the predictor of improving knowledge on the disease and early adoption of available test procedure.An awareness building program should be designed for women of early detection of cervical cancer using VIA procedure.